2013
DOI: 10.1080/14763141.2013.784799
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface traction characteristics on frictional demand and kinematics in tennis

Abstract: The interaction between footwear and surfaces influences the forces experienced by tennis players. The purpose of this study was to investigate traction demand and kinematic adaptation during tennis-specific movements with changes in traction characteristics of surfaces. We hypothesised that players would increase the utilised coefficient of friction (horizontal to vertical ground reaction force ratio) when the shoe surface combination had a high coefficient of friction and flex their knee after contact to fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 21 publications
(19 reference statements)
0
19
0
Order By: Relevance
“…Different methods have been used for estimating movement variability within kinematic and kinetic parameters. Coefficient of variation (CV) and biological coefficient of variation (BCV) are common methods used to observe movement variability of key discrete variables (Queen et al, 2006;Bradshaw et al 2008;Damm, Low, Richardson, Clarke, Carré, & Dixon, 2013). However, the use of discrete variables in the analysis of movement variability may not provide a comprehensive explanation of the observed movement, and thus many potentially informative data may be ignored (Ryan, Harrison, & Hayes, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been used for estimating movement variability within kinematic and kinetic parameters. Coefficient of variation (CV) and biological coefficient of variation (BCV) are common methods used to observe movement variability of key discrete variables (Queen et al, 2006;Bradshaw et al 2008;Damm, Low, Richardson, Clarke, Carré, & Dixon, 2013). However, the use of discrete variables in the analysis of movement variability may not provide a comprehensive explanation of the observed movement, and thus many potentially informative data may be ignored (Ryan, Harrison, & Hayes, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, knee ROM increased in less cushioned surfaces because of its important role to absorb and dissipate the load (Gerritsen et al, 1995). In fact, the increase in knee ROM during the less cushioned surface loads the knee extensors (Damm et al, 2013) and may increase the risk of suffering from patellofemoral pain syndrome (Gecha & Torg, 1988). To reinforce these observations, our present study demonstrated that both knee ROM and extensor moment were higher in less cushioned surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies (e.g. 46,47,48 ) have also highlighted the interactive effect of the footwear with the surface and the importance of the playing surface combination when discussing the effect of playing shoes. As the current study performed the cutting manoeuvre directly onto a force plate, surface conditions were un-representative of normal playing conditions.…”
Section: Discussionmentioning
confidence: 99%